Vertical jump performance and power asessement of Greek junior national level judo athletes - Panoutsakopoulos, V.; Kotzamanidou, M. C.; Aleksandrovi, M.; Kollias, I. A. (FIS communications in Physical Education, Sport and Recreation, 2016)
Muscular strength and power are essential parameters for judo performance. Vertical jumping tests are commonly used to evaluate lower limb strength and power, but biased results occure in the literature about vertical jump performance and power output when judokas are examined. The aim of the present study was to assess vertical jump performance and the power output of junior judo athletes when a countermovement and/or an arm swing is enabled to the jumping technique. Twelve male junior national level judo athletes (age = 17.3 +/- 1.9 yrs; height = 1.70 +/- 0.11 m; mass = 69.7 +/- 18.2 kg) volunteered to participate in the present study. Vertical jumps from a stationary squatting starting position (SQJ), with a countermovement (CMJ), with a countermovement and an arm swing (CMJf) and after dropping from 40 cm (DJ40) were executed on an AMTI force plate. Repeated measures ANOVA revealed that vertical jump performance was significantly (p < .05) increased in CMJ and CMJf compared to SQJ and DJ40. However, no differences (p > .05) were revealed concerning power output normalized to body mass. Average jump height gain due to the countermovement was 20.5%, while the respective gain due to the neuromuscular coordination imposed by the arm swing was 14.1%. It was concluded that the tested biomechanical parameters across the vertical jump tests in the examined judo athletes were not in agreement with the trend reported in the literature, especially in the case of the combined use of an countermovement and an arm swing.